2014
DOI: 10.2176/nmc.oa.2013-0332
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, 10-minute Procedure for Transforaminal Injection under Ultrasonic Guidance to Effect Cervical Selective Nerve Root Block

Abstract: The aim is to provide a detailed procedure of a simple and 10-minute cervical nerve root block (CNRB) under ultrasonic guidance, and to report the clinical outcomes, disorders, and complications. Records of patients who had undergone CNRB, were reviewed under ultrasonic guidance at the hospital from 2010 through 2012. The procedure is described in detail. Arm and shoulder pain was evaluated by use of the visual analogue scale (VAS). Forty-three patients agreed to undergo CNRB under ultrasonic guidance. Nerve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Ultrasound guidance can help identify anatomical variations and thus avoid injury to aberrant vessels [19,20]. Our study supports the safety profile of this technique with no significant complications experienced by any of our patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Ultrasound guidance can help identify anatomical variations and thus avoid injury to aberrant vessels [19,20]. Our study supports the safety profile of this technique with no significant complications experienced by any of our patients.…”
Section: Discussionsupporting
confidence: 83%
“…Although we do not yet have the long-term follow-up data to clarify how long the effect can last, 26 % of patients had ongoing relief at least six weeks after the procedure. Recent work by Takeuchi et al has shown an average 17-month duration of symptom reduction [20]. In this manner patients, and even some with long-term symptoms, may experience quite significant relief of pain and symptoms with a short and safe procedure that has the potential in some cases to avoid the need for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US could real-time monitor the puncture procedure without ionizing radiation, since it could distinguish bones, nerves, blood vessels and muscles clearly. Ultrasound scanning technology has been gradually applied in orthopedics, such as lumbar facet joint injection and nerve root block [6,7] . Up to date, the safety and e cacy of ultrasound guidance for determining the entry point of PVP puncture has still no report.…”
Section: Introductionmentioning
confidence: 99%
“…1), transforaminal injection or nerve root block [3][4][5], and transforaminal endoscopy [6][7][8][9]. Although usually care is taken with nerves, the blood vessels and ligaments in the LIF have often been ignored by surgeons, and the dangers or complications of these procedures have also been neglected.…”
Section: Introductionmentioning
confidence: 99%